Evaluation of Mobile Augmented Reality Hearing-Impaired Museum Visitors Engagement Instrument - Esraa Jaffar Baker; Juliana Aida Abu Bakar; Abdul Nasir Zulkifli (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Mobile Augmented Reality has come a long way since its inception as a multimedia system during the last few decades. From the concept of an Augmented Reality experience to actual smartphone applications, it has come a long way. Researchers have chosen to leverage the concept of engagement in the construction of Mobile Augmented Reality applications in order to boost museum visitors’ engagement and provide a more effective learning environment. The majority of Mobile Augmented Reality applications, on the other hand, were designed with normal hearing visitors in mind, while hearing-impaired visitors are given less attention. Those with hearing difficulties have an unfavourable experience as a result of this, and are unsatisfied with their visit. The elements of Mobile Augmented Reality aimed at engaging hearing-impaired museum visitors are determined in this study. The next step was to construct a conceptual model, which was then validated through an expert review. In investigating any flaws of the instrument among hearing-impaired museum visitors, a pilot study was conducted to improve the items and determine their level of reliability. Participants in the study were hearing-impaired who visited one of Iraq’s ancient museums. This study will focus on evaluating the prototype to see how effective it is at engaging hearing-impaired museum visitors in the near future.